The Strategy to Improve the Competitiveness of Indonesian Seaweeds in Global Market - Delu Damelia; Etty Soesilowati (Muhammadiyah University Press, 2016)
This research is aimed to know the position of Indonesian seaweeds exports’ competitiveness in global market, as well as the strategy to improve it. The research uses a quantitative approach, which specifically employs time series type that has been done within 10 years period (2003-2012). The data used are the data of seaweed product by the code product of HS 121220 Seaweeds and other algae (fresh or dried), HS 121221 Seaweeds fit for human consumption, HS 121229 Seaweeds and other algae unfit for human consumption. The data includes the value of Indonesian seaweeds exports commodity, the total of Indonesian exports, the value of seaweeds in global exports, the total of global exports, Indonesian seaweeds imports, Indonesian seaweeds production, and Indonesian seaweeds exports. The data is analyzed using Revealed Comparative Advantage (RCA), Import Dependency Ratio (IDR), Specialized Trading Index (ISP), Commodity Concentration Index (CCI), alongside with Strengths, Weaknesses, Opportunities, and Threats. The result shows that: (1) The RCA of seaweeds commodity though fluctuating but relatively increasing; (2) The Import Dependency Ratio of Indonesian seaweeds though fluctuating but relatively increasing, the fluctuation is due to their inability to produce plus value of ferments; (3) Index of Specialized trading appears to be positive; (4) Commodity Concentration Index of exports and imports though fluctuating but relatively increasing; (5) Indonesia can employ Rapid Growth Strategy. The result recommends Indonesian government to improve the quality of seaweeds products specifically using distribution improvements from farmers to consumer both in industrial scope and domestic consumer.